Influence of Digital Technologies on the Labor Market of HR Specialists - Shpak, Nestor; Maznyk, Liana; Dvulit, Zoriana; Seliuchenko, Nadiia; Dragan, Olena; Doroshkevych, Kateryna (My University, 2022)
In this paper, we examine the impact of digital technologies on the labor market of HR professionals. With this purpose, digital trends in the creation of new operational processes in personnel management have been studied; the conditions for the implementation of digital technologies have been substantiated; the content of the main stimulants that contribute to the implementation of digital technologies in personnel management has been determined. The importance of digital culture as the basis of the organization’s corporate culture according to the trends of world digital culture is emphasized; the influence of stimulants on the state of the labor market of HR specialists is assessed. The study is based on an array of official statistical information from the State Employment Service of Ukraine. The applied methodology of taxonomy made it possible to determine the degree of balance of the labor market of HR specialists in Ukraine in January 2020 - October 2021. And this methodically ensures monitoring of the situation in the labor market of specialists in the field as a whole. Factors that balanced the indicators of vacancies and unemployment in the labor market were identified. Recommendations have been formulated for the relevant state institutions that will help improve the situation in the labor market of HR specialists. In this paper, we consider the expert opinions of HRM practitioners who believe that the possession of relevant digital competencies for employees in this field is a basic condition for the formation of a modern labor market of HR professionals, confirming our results and conclusions. У цій роботі ми досліджуємо вплив цифрових технологій на ринок праці HR-фахівців. З цією метою досліджено цифрові тенденції створення нових операційних процесів в управлінні персоналом; обґрунтовано умови впровадження цифрових технологій; визначено зміст основних стимуляторів, що сприяють впровадженню цифрових технологій в управлінні персоналом. Підкреслено важливість цифрової культури як основи корпоративної культури організації відповідно до тенденцій світової цифрової культури; оцінено вплив стимуляторів на стан ринку праці спеціалістів з персоналу. Дослідження базується на масиві офіційної статистичної інформації Державної служби зайнятості України. Застосована методологія систематики дозволила визначити ступінь збалансованості ринку праці кадрів в Україні за січень 2020 – жовтень 2021 років. А це методично забезпечує моніторинг ситуації на ринку праці спеціалістів галузі в цілому. . Визначено фактори, що збалансували показники вакансій та безробіття на ринку праці. Сформульовано рекомендації для відповідних державних установ, які сприятимуть покращенню ситуації на ринку праці кадрів. У цій роботі ми розглядаємо експертні думки практиків з управління персоналом, які вважають, що володіння відповідними цифровими компетенціями для працівників у цій сфері є основною умовою формування сучасного ринку праці HR-спеціалістів, що підтверджує наші результати та висновки.
Keywords: кафедра економіки праці та менеджменту; digital technologies; labor market; personnel management; taxonomy; діджитал технології; ринок праці; HR-система; менеджмент персоналу; таксономія